THE EFFECT OF IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEMS, INTERNAL SUPERVISION, AND REWARD ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS MODERATING VARIABLES IN SERDANG BEDAGAI DISTRICT - Sonia, Jihan (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study was to analyze the effect of Accounting Information Systems, Internal Control and Reward on employee performance with motivation to work as a moderating variable in Serdang Bedagai Regency. This type of research is causal research. The population in this study were 93 people, consisting of the Head of Office, Secretary of the Head of Office and Head of Finance. The method of determining the sample with the census method, so that the entire population is used as a research sample. The data in this study are primary data and data collection techniques using a questionnaire. Hypothesis testing uses the Structural Equation Model (SEM) with the help of the Partial Least Square (PLS) program. The results of this study prove that accounting information systems, internal controls and rewards have a positive effect on employee performance in Sergai Regency. Motivation to work as a moderating variable cannot moderate the effect of the accounting information system, internal supervision and rewards on employee performance in Serdang Bedagai District.